Georgia Russell’s Scalpelled Books as Visual Metaphors - Anne Béchard-Léauté (Interfaces)
The presence of the written word in the work of Scottish artist Georgia Russell denotes an attraction for the evocative power of the term. Since her arrival in France, the artist has used the book as a medium, and her cutting technique appropriates different genres, generally textual, known to all. She uses novels, book covers etc., where the scalpel cuts highlight certain terms, while obliterating others. This attachment to the word leads her to create visual short-cuts relating to the dreamlike approach of surrealism or psychoanalysis. Using just the evocative function of a term with universal connotations, a form of imagination develops based on the interaction between art and language. I will show how Georgia Russell appropriates the word to transform it into an almost organic materiality, her paper sculptures becoming veritable totemic figures.